1997
DOI: 10.1016/s0960-0760(96)00237-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Distribution of Aromatase MRNA in the Rat Brain: Indications of Regional Regulation

Abstract: Aromatase, the enzyme responsible for the conversion of testosterone to estradiol, is found in the rat brain and is present in regions of the preoptic area, hypothalamus, and limbic system. Gonadal steroid hormones regulate aromatase activity levels in many brain regions, but not all. Using in situ hybridization, we examined the distribution of aromatase mRNA in the adult male forebrain, as well as the levels of aromatase mRNA in the brains of males and females, and the regulation by gonadal steroid hormones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Together, these observations suggests that if estrogens induce rapid and transient behavioral effects in males, mechanisms must exist to regulate local estrogen concentrations on much shorter time scales. Brain aromatase, which is expressed and active especially in brain regions controlling aggressive and sexual behaviors [14; 49; 93; 137; 226; 227; 229; 233; 234; 280; 282] but also in the hippocampus [14; 226; 229; 233; 239; 240; 260; 282], was thus considered as a potential local source of estrogens. However, due to their lipophilic nature, estrogens cannot be stored in synaptic vesicles before rapid release like classical neurotransmitters or neuropeptides.…”
Section: What Is the Source Of Estrogens?mentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these observations suggests that if estrogens induce rapid and transient behavioral effects in males, mechanisms must exist to regulate local estrogen concentrations on much shorter time scales. Brain aromatase, which is expressed and active especially in brain regions controlling aggressive and sexual behaviors [14; 49; 93; 137; 226; 227; 229; 233; 234; 280; 282] but also in the hippocampus [14; 226; 229; 233; 239; 240; 260; 282], was thus considered as a potential local source of estrogens. However, due to their lipophilic nature, estrogens cannot be stored in synaptic vesicles before rapid release like classical neurotransmitters or neuropeptides.…”
Section: What Is the Source Of Estrogens?mentioning
confidence: 99%
“…The enzyme is mainly expressed in the ovaries but is also found in many other tissues including the brain. In reptiles, birds and mammals, brain aromatase expression is restricted to specific neuronal populations mainly located in the hypothalamic/preoptic area (HPOA) including the medial preoptic nucleus and in the limbic system [11; 49; 60; 93; 136; 137; 169; 226; 227; 228; 229; 233; 234; 240; 260; 280; 282]. In songbird species, aromatase is found in another neuronal population located in the caudomedial nidopallium NCM, a pallial area (homologous to secondary auditory cortex in mammals) adjacent to the song control nucleus HVC (acronym used as proper name [14; 240; 251]).…”
Section: What Is the Source Of Estrogens?mentioning
confidence: 99%
“…This transformation is catalyzed by the enzyme aromatase, also known as CYP 19 or estrogen synthase. In most vertebrates, central aromatase expression is restricted to specific neuronal populations mainly located in the hypothalamic/preoptic areas including the medial preoptic nucleus and in the limbic system (Roselli et al, 1985 ; Foidart et al, 1995a , b ; Wagner and Morrell, 1997 ; Trainor et al, 2007 ; Metzdorf et al, 1999 ; Roselli and Resko, 2001 ). It should be noted that songbirds have an additional population of aromatase expressing neurons in the caudomedial nidopallium, in the telencephalon (NCM; Shen et al, 1995 ; Saldanha et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, experimental evidence has shown that estrogen also protects against nigrostriatal degeneration in the male striatum. However, while circulating estrogen is abundant in females, striatal estrogen available in males is minimal due to the low levels of aromatase in the striatum [6366]. Therefore, the inability of testosterone to act through estrogenic mechanisms effectively prevents hormone-driven neuroprotection in the striatum.…”
Section: Discussionmentioning
confidence: 99%